Co-hydrothermal carbonization of polystyrene waste and maize stover combined with KOH activation to develop nanoporous carbon as catalyst support for catalytic hydrotreating of palm oil - Kaewtrakulchai, Napat; Chanpee, Sirayu; Jadsadajerm, Supachai; Wongrerkdee, Sutthipoj; Manatura, Kanit; Eiad-Ua, Apiluck (My University, 2024)
Plastic waste is massively generated daily from households, mainly as packaging material, causing serious surrounding ecological problems. The development of plastic waste for higher value-added applications instead of landfilling and incineration has received consideration interest in bioenergy and material science research. Herein, a nanoporous carbon support of nickel phosphide catalyst for palm oil hydrotreating was developed from blended polystyrene waste and maize stover via the Co-hydrothermal carbonization (HTC) coupled with the KOH activation process. The Co-HTC parameters, such as temperature, reaction time, and PS percentage, were studied on the properties of co-hydrochar feedstocks for further activation using the Box behnken design. From the comprehensive characterization results, response surface methodology (RSM) results showed that the rising polystyrene proportion significantly exhibited the higher production yield and fixed carbon of co-hydrochar products, an essential characteristic for porous carbon manufacturing. After activation step, the final nanoporous carbon derived from the co-hydrochar (PMPC) exhibited the highest specific surface area of 1033.58 m2/g with total pore volume of 0.45 cm3/g. Moreover, the PCMC-supported nickel phosphide catalysts were successfully synthesized and tested for the catalytic hydrotreating of palm oil as alternative catalyst. The NiP-PMPC catalyst represents an impressive liquid hydrocarbon yield of 74.68 % with a high green diesel selectivity of 85.92 % at 100 % palm oil conversion. The findings of this study might help develop and utilize blended plastic waste and agricultural waste as an alternate catalytic support for various processes in biofuel and biochemical synthesis.
Keywords: Catalytic hydrotreating; Co-hydrothermal carbonization; Maize stover; Nanoporous carbon; Polystyrene